Fossil Fuel Interests in Environmental and Climate Policy: Evidence of Influence and Institutionalised Participation - Saydon, Giulia (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Political Science, 2023)
Do fossil fuel interest groups and companies engage in systematic participation in institutions of state-society relations such as public consultations in pursuit of policy influence in the area of environment and climate? This question is informed by evidence from lobbying and energy transition literatures and by insights from policy analysis and constitutes the starting point of this dissertation. It is argued that the organisational advantages of fossil fuel actors make them likely to use public consultations in their pursuit of influence over environmental and climate issues, and that these also make them more likely to participate than groups representing diffuse interests (like environmental groups). It is also argued that fossil fuel interest groups benefiting from actor-level organisational advantages are more likely to participate than individual companies and that fossil fuel actors are generally more likely to participate when the policy being proposed entails targeted coercive measures than when it does not. The existence of this pattern of participation is assessed in two countries selected from an OECD sample using process-tracing and statistical methods applied to consultation data. In the UK, a typical case, evidence is found of fossil fuel embeddedness in the process, but not of the hypothesised pattern of systematic and strategic participation. In Denmark, a deviant case, there is insufficient evidence not only of pattern but also of embeddedness, leading to exploration of avenues of theoretical and empirical refinement and pointing to the potential role of signals of policy commitment as a mitigator of the pursuit of influence by such actors. Arguments regarding influence-seeking patterns of participation are also translated into ones regarding patterns of political influence in search of an answer to the question of whether political-economic clout enables fossil fuel industries to negatively influence environmental and climate policy. This question is motivated by the pursuit of a framework more conducive to the identification of influence, which I construct using saliency theory as an empirical bedrock. I hypothesise that the political-economic clout of fossil fuel industries moderates governments? ability to fulfil their environmental and climate mandates, and that this effect is felt more strongly on policy instruments that entail targeted coercive measures than on ones that do not. This argument is tested on a panel of OECD data, where evidence of influence, and of the differential effect of different forms of coercive instruments, is identified.
APPROVED
Keywords: Climate; Public Consultations; Fossil Fuels; Energy Transition; Lobbying; Policy Analysis; Interest Groups; Environment; Collective Action; Saliency Theory; OECD; UK; Denmark